(untitled) (Commonwealth Journal of Local Governance, 2015)
This paper examines the process of the formulation of decentralised planning in the Tribal regions of Odisha, a state located in eastern part of India, while examining the powers devolved to the local governments in such regions in the state to formulate plan, and the ground reality of the preparation of such plans in the context of the implementation of the Provisions of Panchayats (Extension to Scheduled Areas) Act (PESA Act). Formulation of decentralised planning in Odisha was taken up in the year 2008. However, based on the secondary data and interacting with the various people in field, the paper has revealed that “structural impediments” and “functional incapacity” of the local governments in the Scheduled Areas have hampered the spirit of such institutions with regard to the planning and implementation of the development programs. The paper argues that decentralised plans should be realistic, based on the effective utilisation of local resources, and the local development issues should be prioritised and implemented accordingly. The paper suggests policy measures such as effective participation, prioritisation of development needs, and rationalisation of the required and available funds, considering the significance of the PESA Act. While doing so, the issues of the tribals should receive priority.